A good strength-ductility match in Cu-Mn alloys with high stacking fault energies: Determinant effect of short range ordering. (May 2017) - Han, D.; Wang, Z.Y.; Yan, Y.; Shi, F.; Li, X.W.
Abstract: The tensile tests were conducted to investigate the influence of short-range order (SRO) on the mechanical properties and deformation microstructures in coarse-grained Cu-Mn alloys with high stacking fault energies. Tensile testing results demonstrate that a good strength-ductility match in Cu-Mn alloys can be achieved by increasing degree of SRO (namely increasing Mn content). With increasing SRO of alloys, the deformation micromechanisms were gradually transformed from wavy slip of dislocations to planar slip of dislocations and deformation twinning, resulting in a synchronous improvement of strength and ductility of Cu-Mn alloys. Graphical abstract: